2020
DOI: 10.3390/app10186625
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Harmony Search-Simulated Annealing Algorithm for Location-Inventory-Routing Problem in Supply Chain Network Design with Defect and Non-Defect Items

Abstract: This paper considers a location-inventory-routing problem (LIRP) that integrates the strategic, tactical, and operational decision planning in supply chain network design. Both defect and non-defect items of returned products are considered in the cost of reverse logistics based on the economic production quantity model. The objective of the LIRP is to minimize the total cost of location-allocation of established depots, the cost of inventory, including production setup and holding cost, as well as the cost of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The optimization process in HS is a mimicry of the underpinning principles of jazz music orchestra, where musicians attain a pleasant harmony through several improvisation steps. HS has been successfully applied to a wide variety of real-world optimization problems, such as system reliability, robot path planning, renewable energy systems, hyper-parameter tuning of deep neural networks, intelligent manufacturing, and credit scoring (see [35,36]); university timetabling, structural design, water distribution, and supply chain management (see [37,38]); and, music composition, Sudoku puzzle solving, tour planning, web page clustering, vehicle routing, dam scheduling, groundwater modeling, soil stability analysis, ecological conservation, heat exchanger design, transportation energy modeling, satellite heat pipe design, medical physics, medical imaging, RNA structure prediction, and image segmentation (see [39], among others). Besides that, the implementation of HS in various parameter estimation studies indicated the potentiality of HS as an effective parameter estimation tool.…”
Section: Harmony Search Algorithm and Selected Variantsmentioning
confidence: 99%
“…The optimization process in HS is a mimicry of the underpinning principles of jazz music orchestra, where musicians attain a pleasant harmony through several improvisation steps. HS has been successfully applied to a wide variety of real-world optimization problems, such as system reliability, robot path planning, renewable energy systems, hyper-parameter tuning of deep neural networks, intelligent manufacturing, and credit scoring (see [35,36]); university timetabling, structural design, water distribution, and supply chain management (see [37,38]); and, music composition, Sudoku puzzle solving, tour planning, web page clustering, vehicle routing, dam scheduling, groundwater modeling, soil stability analysis, ecological conservation, heat exchanger design, transportation energy modeling, satellite heat pipe design, medical physics, medical imaging, RNA structure prediction, and image segmentation (see [39], among others). Besides that, the implementation of HS in various parameter estimation studies indicated the potentiality of HS as an effective parameter estimation tool.…”
Section: Harmony Search Algorithm and Selected Variantsmentioning
confidence: 99%
“…is algorithm is compared with the existing methods in order to verify the effectiveness of this method. Comparison methods are standard ICA and hybrid harmonic search-simulated annealing (HS-SA) algorithm proposed in [17]. e HS-SA algorithm combines the dynamic value of harmony memory considering the speed and pitch adjustment rate with local optimization technology and combines the idea of probability acceptance rule of simulated annealing to avoid local extreme points.…”
Section: Cost Functionmentioning
confidence: 99%
“…Several attempts have been made in the literature to hybridize the original and enhanced HSA with other local search algorithms to improve its performance [5]. The HSA has been hybridized with other heuristic-based algorithms, such as hillclimbing [6,7], great deluge [8], simulated annealing [9,10], and particle swarm optimization [11]. For the process of diversification and intensification, the hybridization of population-based methods with local search-based methods has been considered by many researchers to strike the balance between these processes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%